Alternative patterns of deep brain stimulation in neurologic and neuropsychiatric disorders - Najera, Ricardo A.; Mahavadi, Anil K.; Khan, Anas U.; Boddeti, Ujwal; Del Bene, Victor A.; Walker, Harrison C.; Bentley, J. Nicole (Frontiers in Neuroinformatics, 2023)
Deep brain stimulation (DBS) is a widely-used clinical therapy that modulates neuronal firing in subcortical structures, eliciting downstream network effects. Its effectiveness is determined by electrode geometry and location as well as adjustable stimulation parameters including pulse width, interstimulus interval, frequency, and amplitude. These parameters are often determined empirically during clinical or intraoperative programming and can be altered to an almost unlimited number of combinations. Conventional high-frequency stimulation uses a continuous high-frequency square-wave pulse (typically 130-160 Hertz), but other stimulation patterns may prove efficacious, such as continuous or bursting theta-frequencies, variable frequencies, and coordinated reset stimulation. Here we summarize the current landscape and potential clinical applications for novel stimulation patterns.